Monumenta Studien zu mittel- und späthelladischen Gräbern in Messenien - Zavadil, Michaela (Verlag der Österreichischen Akademie der Wissenschaften, 2014)
Messenia was one of the core areas of the Middle and Late Helladic culture in Greece. Based on a catalogue of 57 sites, which comprises about 240 tombs, their topographic situation, architectural design and the offerings found in them are analysed. This work provides a contribution to a better understanding of the social hierarchy and political changes in these phases of Greek prehistory.